Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Dan Free Cash Flow Sebagai Variabel Moderating Pada Perusahaan Freeport Indonesia, Tbk - Yesa Cahayaning Ramadhani (Jurnal Manajemen dan Keuangan, 2020)
The purpose of this study is to test and analyze the Effect of Capital Structure, Liquidity, Profitability And Value Of Companies And Free Cash Flow As Moderating Variables. The population in this study is a Freeport company registered with FCX. The technique of determining the sample is done by using purposive sampling technique, based on certain criteria that is to publish the financial statement as per December 31 which is complete in succession especially in 2004 - 2016 Company which always distributes its dividend in succession during 2004 - 2016. The data source used is secondary data obtained from Annual Report in FCX Global America (Online). Hypothesis testing of research using multiple linear regression analysis technique and MRA Residual. The results showed that: 1). Capital Structure has no significant effect on Corporate Value, 2). Liquidity significantly affects Corporate Value, 3). Profitability has no significant effect on Corporate Value, 4). Free Cash Flow is not able to significantly moderate the Influence of Capital Structure, Liquidity and Profitability to Corporate Value